Predictive Machine Learning Models for Effective Resource Utilization Forecasting in Hybrid IT Systems - Subba Rao Katragadda; Ajay Tanikonda; Sudhakar Reddy Peddinti; Brij Kishore Pandey (Journal of Science & Technology, 2022)
The rapid proliferation of hybrid IT systems, encompassing both on-premises infrastructure and cloud-based solutions, has necessitated the development of advanced predictive methodologies to optimize resource utilization. Inefficient resource allocation often leads to operational bottlenecks, cost overruns, and degraded performance, underscoring the need for precise forecasting mechanisms. This paper delves into the role of predictive machine learning (ML) models in addressing these challenges by forecasting resource utilization with high accuracy in hybrid IT environments. Hybrid systems, characterized by their dynamic and heterogeneous nature, require specialized models capable of adapting to variable workloads, fluctuating demand patterns, and disparate infrastructure specifications. We provide a comprehensive analysis of machine learning algorithms and their suitability for resource utilization forecasting, with an emphasis on supervised learning techniques such as regression, time-series analysis, and ensemble methods. Models like Long Short-Term Memory (LSTM) networks, gradient boosting algorithms, and autoregressive integrated moving average (ARIMA) are evaluated for their efficacy in predicting resource consumption metrics such as CPU usage, memory allocation, disk I/O, and network bandwidth. Furthermore, unsupervised learning approaches such as clustering and anomaly detection are discussed in the context of identifying usage patterns and deviations that inform resource allocation strategies. To bridge theoretical insights with practical applications, we highlight case studies showcasing the deployment of ML-driven forecasting models in hybrid IT systems. These examples demonstrate the tangible benefits of such models, including reduced over-provisioning, cost optimization, and enhanced system reliability. A critical evaluation of the underlying data prerequisites is also provided, focusing on data quality, granularity, and the integration of data streams from disparate sources. The paper underscores the importance of preprocessing techniques, such as normalization, feature extraction, and dimensionality reduction, in ensuring robust model performance. Challenges associated with the implementation of predictive ML models in hybrid IT environments are rigorously examined. These include the computational overhead of training complex models, scalability issues when extending predictions across multi-cloud or hybrid landscapes, and the interpretability of model outputs. Additionally, ethical and governance considerations, such as ensuring data privacy and compliance with regional data regulations, are discussed as essential components of the implementation framework. Emerging trends in the domain are explored, with a focus on the integration of federated learning for collaborative model training without compromising data sovereignty, and the potential of explainable AI (XAI) techniques to enhance the interpretability and trustworthiness of forecasting models. Moreover, we analyze the implications of these advancements for resource orchestration in hybrid IT systems, emphasizing real-time adaptability and decision-making capabilities. By synthesizing existing research and presenting practical insights, this study establishes a roadmap for leveraging predictive machine learning models to achieve effective resource utilization forecasting in hybrid IT systems. The findings have significant implications for IT administrators, system architects, and organizational stakeholders seeking to enhance operational efficiency while maintaining cost-effectiveness. Future research directions are proposed, including the exploration of transfer learning for cross-environment adaptability, the development of lightweight models for edge computing contexts, and the alignment of predictive frameworks with evolving hybrid IT paradigms.